Developing a Competency‐based Curriculum in Basic and Clinical Pharmacology – A Delphi Study among Physicians. Issue 6 (22nd July 2015) - Midlöv, Patrik; Höglund, Peter; Eriksson, Tommy; Diehl, Annika; Edgren, Gudrun
Abstract: A new curriculum is planned for the medical school at Lund University, Sweden. Pharmacology, in a broad sense, has been identified as a subject that needs to be strengthened based on needs in the healthcare system. The aim was to identify the competencies in basic and clinical pharmacology that a newly qualified physician needs. Using a modified three‐round Delphi technique, 31 physicians were invited to list necessary competencies (round 1). After content analysis, these panel members classified the list by importance on two occasions (rounds 2 and 3) using a 4‐point scale (4 = necessary, 3 = desirable, 2 = useful, 1 = not necessary). Competencies with the highest ranks based on necessity were retained. Thirty physicians accepted the invitation and 25 (83%) of them completed all three rounds. Round 1 resulted in 258 suggestions, which were subsequently reduced to 95 competencies. Of these 95 competencies, 40 were considered necessary by at least 75% of the panel members. The degree of consensus increased between round 2 and round 3. Using a modified Delphi technique, we identified 40 competencies that could be transferred to learning outcomes for a new curriculum in basic and clinical pharmacology at medical school.